Modeling Micro-Scale Heatwaves: Thermal Dynamics of a Contained Infrared Dryer Using Specular Reflectors - Savindra Atharizqi Arifin; Afkar Khaizuran Hamiz Habibie; Muhammad Javier Alfarezel; Reynald Fathullah Zunnurain; Rakan Tsaqif; Nisrina Meta Gamanik (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
This research analyzes and models the thermal dynamics of a low-cost, contained dryer system designed to optimize infrared heat transfer. The concept of a “micro-scale heatwave” is introduced to describe the concentrated and controlled thermal environment within the system. An experimental method was employed through the construction of a prototype using an incandescent bulb as an infrared heat source and aluminum foil as a specular reflector. System performance was evaluated by comparing dehydration rates, temperature distribution, and energy consumption between a configuration with the reflector and a control configuration without the reflector. The results indicate that the use of a specular reflector reduces average drying time by up to 41% and increases the temperature at the target material by approximately 22%, while maintaining nearly identical energy consumption. These findings demonstrate that internal surface modification using reflective materials is an effective strategy for enhancing infrared heat transfer efficiency in small-scale thermal systems.